The province of legislation determined : legal theory in eighteenth-century Britain / David Lieberman. - Lieberman, David, 1953- (Ideas in context, 1989)
A comprehensive account of English legal thought in the age of Blackstone and Bentham for nearly a century, The Province of Legislation Determined advances an ambitious reinterpretation of eighteenth-century attitudes to social change and law reform. Professor Lieberman's bold synthesis rests on a wide survey of legal materials and on a detailed discussion of Blackstone's Commentaries, the jurisprudence of Lord Kames and the Scottish Enlightenment, the chief justiceship of Lord Mansfield, the penal theories of Eden and Romilly, and the legislative science of Jeremy Bentham. The study relates legal developments to the broader fabric of eighteenth-century social and political theory, and offers a novel assessment of the character of the common law tradition and of Bentham's contribution to the ideology of reform.